2017
DOI: 10.1039/c6ee02801b
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic and bioinspired approaches for wiring enzymes to electrode interfaces

Abstract: Our review focuses on biomimetic and bioinspired ideas to improve enzyme-driven bioelectrochemical systems for applications in energy, biomedical and environmental fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 297 publications
0
57
0
Order By: Relevance
“…Many hydrogenases oxidize and produce hydrogen at very high rates (in excess of thousands per second, table 4 in ref [75]), and therefore a catalytic current may be detected even if the amount of enzyme that is attached to the electrode is very low. This explains the diversity of electrode materials that have proven useful in this context, listed in table 1 (see also refs [76][77][78] for reviews). Finely designed architectures for embedding membrane-bound hydrogenases have also been developed [79][80][81].…”
Section: Electrodes For Direct Electron Transfermentioning
confidence: 99%
“…Many hydrogenases oxidize and produce hydrogen at very high rates (in excess of thousands per second, table 4 in ref [75]), and therefore a catalytic current may be detected even if the amount of enzyme that is attached to the electrode is very low. This explains the diversity of electrode materials that have proven useful in this context, listed in table 1 (see also refs [76][77][78] for reviews). Finely designed architectures for embedding membrane-bound hydrogenases have also been developed [79][80][81].…”
Section: Electrodes For Direct Electron Transfermentioning
confidence: 99%
“…The influence of ionic strength as well as various cationic and anionic species on enzymes has already been proven to modulate enzymatic activity or stability in different ways [ 56 , 57 ]; e.g., CDH has two redox domains connected through a flexible linker [ 58 – 60 ], with an ET mechanism similar to FDH but with only one heme in its cytochrome domain as electron acceptor. Moreover, Sezer et al showed an increase in terms of catalytic current of SOx by increasing the ionic strength of the buffer solution [ 61 ], while Feng et al reported on the influence of the viscosity on the rate of the IET [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Full EFCs with a maximum power density (P max ) greater than 1 mW cm -2 Glucose Moreover, as a typical enzyme-catalyzed system, EFCs suffer from poor operational stability, resulting in short lifetimes and higher costs. 77,78 Instability arises not just with the enzyme, but also arises from the use of cofactors such as nicotinamide adenine dinucleotide (NAD + ), adenosine triphosphate (ATP), and coenzyme A (CoA), which are necessary for many redox enzymes, and of other components that include mediators. The complexity of biological systems can pose additional detrimental effects on the stability of EFCs, such as biofouling of the electrode in implantable EFCs, or enzyme inhibition by O 2 for H 2 /O 2 EFCs.…”
Section: Identification Of Main Challenges In Efcsmentioning
confidence: 99%